2006
DOI: 10.1080/00140130600612671
|View full text |Cite
|
Sign up to set email alerts
|

Speech acts, communication problems, and fighter pilot team performance

Abstract: Two aspects of team communication, speech acts and communication problems, and their relation to team performance in a team air combat simulator were studied. The purpose was to enhance the understanding of how team performance is related to team communication. Ten Swedish fighter pilots and four fighter controllers of varying experience participated. Data were collected during fighter simulator training involving four pilots and one fighter controller in each of two teams. Speech acts were collapsed over seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
1
7
1
Order By: Relevance
“…The present study raises further questions around the importance and nature of communication strategies within ad hoc teams. While the study findings suggest that an increased frequency of closing the loop plays a key role in team performance, previous findings suggest that teams that communicate more frequently and explicitly but do so in an inefficient, uncoordinated, or dysfunctional way are more likely to commit errors and experience performance degradation (Patrashkova-Volzdoska, McComb, Green, & Compton, 2003; Serfaty, Entin, & Johnston, 1998; Svensson & Andersson, 2006). The outcomes of the present research suggest that it is a greater frequency of specific communication strategies such as closing the loop that is likely to have a positive impact on ad hoc team performance.…”
Section: Discussioncontrasting
confidence: 62%
“…The present study raises further questions around the importance and nature of communication strategies within ad hoc teams. While the study findings suggest that an increased frequency of closing the loop plays a key role in team performance, previous findings suggest that teams that communicate more frequently and explicitly but do so in an inefficient, uncoordinated, or dysfunctional way are more likely to commit errors and experience performance degradation (Patrashkova-Volzdoska, McComb, Green, & Compton, 2003; Serfaty, Entin, & Johnston, 1998; Svensson & Andersson, 2006). The outcomes of the present research suggest that it is a greater frequency of specific communication strategies such as closing the loop that is likely to have a positive impact on ad hoc team performance.…”
Section: Discussioncontrasting
confidence: 62%
“…Other authors have discussed the importance of specific speech types within the broader team communications events. For example, Svensson and Andersson (2006) reported that communication types such as metacommunication and tactics were observed more often in winning teams. Urban, Bowers, Monday, and Morgan (1995) reported that effective teams asked fewer questions and fewer "implied questions" than did ineffective teams.…”
Section: Monitoring Behaviorsmentioning
confidence: 99%
“…Additionally, the merits of simulations of individual and team performance have been demonstrated within other research contexts having operational significance to such settings as train driver training [14], fighter pilot and fighter controller training [15], and radar monitoring [16]. Although the laboratory environment cannot duplicate in all respects the isolation, confinement, conflicts, and stressful conditions of naturalistic exploration of remote regions, a challenging simulation scenario as adopted in the present research can create functional behavioral demands and conflicts to which changes in the proposed psychosocial adaptation and performance effectiveness measures would be sensitive.…”
Section: Introductionmentioning
confidence: 98%